Liquid crystal display device and polarizing plate

By using a polyester film with specific retardation and reflection layers, and a broad-spectrum backlight source, the issue of rainbow-like color spots in LCDs is addressed, enhancing visibility.

JP2025015570AActive Publication Date: 2025-01-30TOYOBO CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
JP2024196550
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2015-03-04
Filing Date
2024-11-11
Publication Date
2025-01-30
Estimated Expiration
2035-11-20

AI Technical Summary

Technical Problem

The use of polyester film as a polarized protection film in LCDs leads to the occurrence of rainbow-like color spots due to changes in the polarized state when light passes through, especially with light sources having a narrow peak emission spectrum like those containing excitation light and quantum dots.

Method used

Employing a polyester film with a specific retardation of 1500 to 30000 nm and incorporating reflection anti-reflection layers to maintain the polarized state, combined with a backlight light source having a broad light emission spectrum and narrow peak half-width, to suppress rainbow-like color spots.

Benefits of technology

Significantly reduces rainbow-like color spots across various observation angles, ensuring improved visibility in LCD displays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015570000002
    Figure 2025015570000002
  • Figure 2025015570000003
    Figure 2025015570000003
  • Figure 2025015570000004
    Figure 2025015570000004
Patent Text Reader

Abstract

To provide a liquid crystal display device having a backlight light source that includes a light source and a quantum dot for emitting excitation light, with which rainbow spots are suppressed even when a polyester film is used as a polarizer protective film.SOLUTION: Provided is the liquid crystal display device comprising the backlight light source, two polarizing plates, and a liquid crystal cell arranged between the two polarizing plates, the backlight light source including the light source and the quantum dot for emitting excitation light. At least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer, the polyester film having a retardation of 1500 to 30000 nm, with an anti-reflection layer and / or a low-reflection layer laminated on at least one surface of the polyester film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a liquid crystal display device and a polarizing plate, and more particularly to a liquid crystal display device and a polarizing plate in which the occurrence of rainbow-like color spots is reduced. [Background technology]

[0002] A polarizing plate used in a liquid crystal display (LCD) has a structure in which a polarizer made of polyvinyl alcohol (PVA) or the like dyed with iodine is sandwiched between two polarizer protective films, and triacetyl cellulose (TAC) films are used as the polarizer protective films in most cases. In recent years, as LCDs become thinner, there is a demand for thinner polarizing plates. However, when the thickness of the TAC film used as a protective film is reduced for this purpose, problems arise in that sufficient mechanical strength cannot be obtained and moisture permeability is deteriorated. In addition, TAC films are very expensive, and polyester films have been proposed as an inexpensive alternative material (Patent Documents 1 to 3), but there is a problem in that rainbow-like color spots are observed.

[0003] When an oriented polyester film with birefringence is placed on one side of a polarizer, the linearly polarized light emitted from the backlight unit or polarizer changes its polarization state as it passes through the polyester film. The transmitted light exhibits interference colors specific to the retardation, which is the product of the birefringence and thickness of the oriented polyester film. Therefore, when a cold cathode tube or hot cathode tube with a discontinuous emission spectrum is used as a light source, the transmitted light intensity varies depending on the wavelength, resulting in rainbow-like color spots (see: Proceedings of the 15th Micro-Optical Conference, pages 30-31).

[0004] As a means for solving the above problems, it has been proposed to use a white light source having a continuous and wide emission spectrum, such as a white light emitting diode, as a backlight source, and further to use an oriented polyester film having a certain retardation as a polarizer protective film (Patent Document 4). A white light emitting diode has a continuous and wide emission spectrum in the visible light range. Therefore, it has been proposed that, focusing on the envelope shape of the interference color spectrum of the transmitted light that has passed through a birefringent body, a spectrum similar to the emission spectrum of the light source can be obtained by controlling the retardation of the oriented polyester film, making it possible to suppress rainbow spots.

[0005] By making the orientation direction of the oriented polyester film and the polarization direction of the polarizing plate perpendicular or parallel to each other, the linearly polarized light emitted from the polarizer passes through the oriented polyester film while maintaining its polarized state. In addition, by controlling the birefringence of the oriented polyester film to enhance the uniaxial orientation, light incident from an oblique direction also passes through while maintaining its polarized state. When the oriented polyester film is viewed obliquely, there is a shift in the orientation main axis direction compared to when viewed from directly above, but if the uniaxial orientation is high, the shift in the orientation main axis direction when viewed obliquely is small. For this reason, it is considered that the shift between the direction of the linearly polarized light and the orientation main axis direction is small, making it difficult for the polarization state to change. In this way, it was considered that by controlling the emission spectrum of the light source, the orientation state of the birefringent body, and the orientation main axis direction, the change in the polarization state is suppressed, and the visibility is significantly improved without the occurrence of rainbow-like color spots. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2002-116320 A [Patent Document 2] JP 2004-219620 A [Patent Document 3] JP 2004-205773 A [Patent Document 4] WO2011 / 162198 Summary of the Invention [Problem to be solved by the invention]

[0007] When a liquid crystal display device is industrially produced using a polarizing plate using a polyester film as a polarizer protective film, the transmission axis of the polarizer and the fast axis of the polyester film are usually arranged to be perpendicular to each other. This is due to the following reasons. The polyvinyl alcohol film, which is a polarizer, is manufactured by longitudinal uniaxial stretching. Therefore, the polyvinyl alcohol film used as a polarizer is usually a film that is long in the stretching direction. On the other hand, the polyester film, which is its protective film, is manufactured by longitudinal stretching and then transverse stretching, so that the orientation main axis direction of the polyester film is the transverse direction. In other words, the orientation main axis of the polyester film used as a polarizer protective film is approximately perpendicular to the longitudinal direction of the film. These films are usually laminated together so that their longitudinal directions are parallel to each other to manufacture a polarizing plate. Then, the fast axis of the polyester film and the transmission axis of the polarizer are usually perpendicular to each other. In this case, the rainbow-like color spots are significantly improved by using an oriented polyester film having a specific retardation as the polyester film and using a light source having a continuous and wide emission spectrum such as a white LED as the backlight light source. However, when the backlight source is composed of a light source that emits excitation light and a light-emitting layer that contains quantum dots, a new problem of rainbow spots still occurs.

[0008] In recent years, in addition to the white light source using quantum dot technology, liquid crystal display devices have been developed in which the emission spectrum of the white light source has a clear relative emission intensity peak in each wavelength region of R (red), G (green), and B (blue). For example, liquid crystal display devices that support a wide color gamut have been developed using various types of light sources, such as a phosphor-based white LED light source using a phosphor that has a clear emission peak in the R (red) and G (green) regions by excitation light and a blue LED, a three-wavelength white LED light source, and a white LED light source combined with a red laser. All of these white light sources have a narrower half-width of the peak compared to the light source consisting of a white light-emitting diode using a YAG-based yellow phosphor that has been widely used in the past. It was discovered that these white light sources have the same problems as those of the liquid crystal display device having a backlight light source consisting of a light source that emits the above-mentioned excitation light and a light-emitting layer containing quantum dots when a polyester film having retardation is used as a polarizer protective film that is a component of a polarizing plate.

[0009] In other words, one object of the present invention is to provide a liquid crystal display device and a polarizing plate in which rainbow spots are suppressed in a liquid crystal display device having a backlight light source in which the half-width of each peak in the emission spectrum is relatively narrow, such as a light source that emits excitation light and a backlight light source that includes quantum dots, even when a polyester film is used as a polarizer protective film. [Means for solving the problem]

[0010] Representative aspects of the present invention are as follows. Section 1. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, The backlight light source includes a light source that emits excitation light and quantum dots, At least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer, The polyester film has a retardation of 1500 to 30000 nm, An antireflection layer and / or a low reflection layer is laminated on at least one surface of the polyester film. LCD display device. Section 2. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, the backlight light source emits light having a peak top of an emission spectrum in each of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 780 nm or less, and the half-width of each peak is 5 nm or more; At least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer, The polyester film has a retardation of 1500 to 30000 nm, An antireflection layer and / or a low reflection layer is laminated on at least one surface of the polyester film. LCD display device. Section 3. 3. The liquid crystal display device according to item 2, wherein the backlight light source has emission spectrum peak tops in the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 750 nm, and the half width of each peak is 5 nm or more. Section 4. 4. The liquid crystal display device according to any one of items 1 to 3, wherein the surface reflectance of the antireflection layer at a wavelength of 550 nm is 2.0% or less. Section 5. A polarizing plate having a polyester film laminated on at least one surface of a polarizer, The polyester film has a retardation of 1500 to 30000 nm, and an antireflection layer and / or a low reflection layer are laminated on at least one surface of the polyester film. A polarizing plate for a liquid crystal display device, comprising a light source that emits excitation light and a backlight source that contains quantum dots. Section 6. A polarizing plate having a polyester film laminated on at least one surface of a polarizer, The polyester film has a retardation of 1500 to 30000 nm, and an antireflection layer and / or a low reflection layer are laminated on at least one surface of the polyester film. A polarizing plate for a liquid crystal display device having a backlight light source with an emission spectrum having peak tops in the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm, and the half-value width of each peak is 5 nm or more. Section 7. Item 7. The polarizing plate according to item 5 or 6, wherein the surface reflectance of the antireflection layer at a wavelength of 550 nm is 2.0% or less. Effect of the Invention

[0011] The liquid crystal display device and polarizing plate of the present invention can ensure good visibility with the occurrence of rainbow-like color spots being significantly suppressed at any observation angle. [Brief description of the drawings]

[0012] [Figure 1] An example where multiple peaks exist within a single wavelength region is shown. [Diagram 2] An example where multiple peaks exist within a single wavelength region is shown. [Diagram 3] An example where multiple peaks exist within a single wavelength region is shown. [Figure 4] An example where multiple peaks exist within a single wavelength region is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Generally, a liquid crystal display device has, in the order from the side where a backlight source (also called a "backlight unit") is arranged to the side where an image is displayed (the viewing side), a rear module, a liquid crystal cell, and a front module. The rear module and the front module are generally composed of a transparent substrate, a transparent conductive film formed on the surface on the liquid crystal cell side, and a polarizing plate arranged on the opposite side. That is, in the rear module, the polarizing plate is arranged on the side facing the backlight source, and in the front module, the polarizing plate is arranged on the side where an image is displayed (the viewing side).

[0014] The liquid crystal display device of the present invention is composed of at least a backlight light source and a liquid crystal cell disposed between two polarizing plates. The backlight light source preferably has an emission spectrum having peak tops in the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm, and the half-width of each peak is 5 nm or more. It is known that the peak wavelengths of blue, green, and red defined in the CIE chromaticity diagram are 435.8 nm (blue), 546.1 nm (green), and 700 nm (red), respectively. The wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm correspond to the blue region, green region, and red region, respectively. Examples of light sources having the above-mentioned emission spectrum include a light source that emits excitation light and a backlight light source that includes at least quantum dots. Other examples include a phosphor-based white LED light source that combines a phosphor having emission peaks in the R (red) and G (green) regions by excitation light with a blue LED, a three-wavelength white LED light source, and a white LED light source that combines a red laser. Red phosphors among the phosphors include, for example, nitride phosphors having a basic composition of CaAlSiN3:Eu, etc., sulfide phosphors having a basic composition of CaS:Eu, etc., and silicate phosphors having a basic composition of Ca2SiO4:Eu, etc. Also, green phosphors among the phosphors include, for example, sialon phosphors having a basic composition of β-SiAlON:Eu, etc., and silicate phosphors having a basic composition of (Ba,Sr)2SiO4:Eu, etc.

[0015] The liquid crystal display device may have other components, such as a color filter, a lens film, a diffusion sheet, and an anti-reflection film, as appropriate, in addition to the backlight source, the polarizing plate, and the liquid crystal cell. A brightness enhancement film may be provided between the light source side polarizing plate and the backlight source. An example of the brightness enhancement film is a reflective polarizing plate that transmits one linearly polarized light and reflects linearly polarized light perpendicular to the transmitted light. As the reflective polarizing plate, for example, a brightness enhancement film of DBEF (registered trademark) (Dual Brightness Enhancement Film) series manufactured by Sumitomo 3M Limited is preferably used. The reflective polarizing plate is usually arranged so that the absorption axis of the reflective polarizing plate and the absorption axis of the light source side polarizing plate are parallel to each other.

[0016] Of the two polarizing plates arranged in a liquid crystal display device, at least one of the polarizing plates is preferably a polarizer dyed with iodine such as polyvinyl alcohol (PVA) with a polyester film laminated on at least one surface thereof. From the viewpoint of suppressing rainbow-like color spots, it is preferable that the polyester film has a specific retardation, and an antireflection layer and / or a low reflection layer is laminated on at least one surface thereof. The antireflection layer and / or the low reflection layer may be provided on the surface of the polyester film opposite to the surface on which the polarizer is laminated, or on the surface of the polyester film on which the polarizer is laminated, or both may be provided. It is preferable to provide an antireflection layer and / or a low reflection layer on the surface of the polyester film opposite to the surface on which the polarizer is laminated. When an antireflection layer and / or a low reflection layer is provided on the surface of the polyester film on which the polarizer is laminated, the layer is preferably a polyester film. It is preferable that the polyester film is provided between the film and the polarizer. In addition, other layers (e.g., an easy-adhesion layer, a hard coat layer, an antiglare layer, an antistatic layer, an antifouling layer, etc.) may be present between the antireflection layer and / or the low reflection layer and the polyester film. In order to further suppress rainbow-like color spots, the refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer is preferably 1.53 to 1.62. It is preferable that a film having no birefringence, such as a TAC film, an acrylic film, or a norbornene-based film, is laminated on the other surface of the polarizer (polarizing plate having a three-layer structure), but it is not necessary to laminate a film on the other surface of the polarizer (polarizing plate having a two-layer structure). In addition, when polyester films are used as protective films on both sides of the polarizer, it is preferable that the slow axes of both polyester films are approximately parallel to each other.

[0017] The polyester film may be laminated to the polarizer via any adhesive, or may be laminated directly to the polarizer without any adhesive. The adhesive is not particularly limited and may be any adhesive. As an example, a water-based adhesive (i.e., an adhesive component dissolved or dispersed in water) can be used. For example, an adhesive containing a polyvinyl alcohol resin and / or a urethane resin as a main component can be used. In order to improve adhesion, an adhesive further containing an isocyanate compound and / or an epoxy compound, etc., as necessary, can be used. As another example, a photocurable adhesive can be used. In one embodiment, a solvent-free ultraviolet-curable adhesive is preferred. As a photocurable resin, for example, a mixture of a photocurable epoxy resin and a photocationic polymerization initiator can be mentioned.

[0018] The backlight may be of an edge light type, which uses a light guide plate and a reflector as components, or of a direct type. The backlight light source is preferably a backlight light source having an emission spectrum with a peak top in each wavelength region of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm, and the half-width of each peak is 5 nm or more, with a representative example being a light source that emits excitation light and a backlight light source that contains quantum dots. For example, the quantum dots can be used in the backlight by providing a layer containing a large amount of quantum dots as the light-emitting layer.

[0019] The application of quantum dot technology to LCDs is a technology that has attracted attention in recent years due to the growing demand for an expanded color gamut. LEDs that use normal white LEDs as backlight sources can only reproduce about 20% of the colors in the spectrum that the human eye can recognize. In contrast, when a backlight source is used that consists of a light source that emits excitation light and a light-emitting layer that contains quantum dots, it is said that it is possible to reproduce more than 60% of the colors in the spectrum that the human eye can recognize. Quantum dot technology that has been put into practical use is Nanosys' QDEF TM and QD Vision's Color IQ TM etc.

[0020] The quantum dot-containing light-emitting layer is a layer that contains quantum dots in a resin material such as polystyrene, and emits light of each color on a pixel-by-pixel basis based on the excitation light emitted from the light source. This light-emitting layer is, for example, composed of a red light-emitting layer disposed in the red pixel, a green light-emitting layer disposed in the green pixel, and a blue light-emitting layer disposed in the blue pixel, and the quantum dots in these light-emitting layers of multiple colors generate light of different wavelengths (colors) based on the excitation light.

[0021] Examples of such quantum dot materials include CdSe, CdS, ZnS:Mn, InN, InP, CuCl, CuBr, and Si, and the particle size (size in one direction) of the quantum dots is, for example, about 2 to 20 nm. Among the above quantum dot materials, a red light emitting material may be InP, a green light emitting material may be CdSc, and a blue light emitting material may be CdS. In such a light emitting layer, It has been confirmed that the emission wavelength can be changed by changing the size (particle size) of quantum dots and the composition of the material. The size (particle size) and material of quantum dots are controlled, mixed into resin materials, and applied separately to each pixel. In addition, as the use of heavy metals such as cadmium is being restricted in many applications, cadmium-free quantum dots are also being developed while maintaining the same brightness and stability as conventional ones.

[0022] A blue LED is used as the light source that emits the excitation light, but laser light such as a semiconductor laser may also be used. When the excitation light emitted from the light source passes through the light-emitting layer, an emission spectrum is generated with peaks in the wavelength ranges of 400 nm to less than 495 nm, 495 nm to less than 600 nm, and 600 nm to less than 780 nm. The narrower the half-width of the peak in each wavelength range, the wider the color gamut, but the narrower the half-width of the peak, the lower the luminous efficiency, so the shape of the emission spectrum is designed taking into consideration the balance between the required color gamut and luminous efficiency.

[0023] There are two main mounting methods for light sources using quantum dots, but they are not limited to the following. One is the on-edge method, in which quantum dots are mounted along the end face (side face) of the light guide plate of the backlight. Quantum dots, which are particles with a diameter of several nanometers to several tens of nanometers, are placed in a glass tube with a diameter of several millimeters. The quantum dots are then sealed in a glass tube, which is then placed between the blue LED and the light guide plate. Light from the blue LED is shone onto the glass tube, and the blue light that collides with the quantum dots is converted into green or red light. The on-edge method has the advantage of being able to reduce the amount of quantum dots used, even in large screens. The other method is the surface mounting method, in which the quantum dots are placed on top of the light guide plate. Quantum dots are dispersed in resin and made into a sheet, which is then sandwiched between two barrier films and sealed, and the quantum dot film is then placed on top of the light guide plate. The barrier film serves to prevent deterioration of the quantum dots due to water and oxygen. As with the on-edge method, the blue LED is placed on the edge (side) of the light guide plate. Light from the blue LED enters the light guide plate and becomes a planar blue light, which illuminates the quantum dot film. There are two major advantages to the surface mounting method. The first is that the light from the blue LED passes through the light guide plate and hits the quantum dots, Therefore, the impact of heat from the LED is small, making it easier to ensure reliability. Because it is in film form, it can be easily adapted to a wide range of screen sizes, from small to large.

[0024] In the present invention, the backlight light source preferably has a peak top of the emission spectrum in each of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and less than 780 nm, and the half width of each peak is 5 nm or more. The wavelength region of 400 nm or more and less than 495 nm is more preferably 430 nm or more and less than 470 nm. The wavelength region of 495 nm or more and less than 600 nm is more preferably 510 nm or more and less than 560 nm. The wavelength region of 600 nm or more and less than 780 nm is more preferably 600 nm or more and less than 750 nm, more preferably 630 nm or more and less than 700 nm, and even more preferably 630 nm or more and less than 680 nm. The preferred lower limit of the half width of each peak is 10 nm or more, more preferably 15 nm or more, and even more preferably 20 nm or more. From the viewpoint of ensuring an appropriate color gamut, the upper limit of the half-width of each peak is preferably 140 nm or less, more preferably 120 nm or less, more preferably 100 nm or less, more preferably 80 nm or less, even more preferably 60 nm or less, and even more preferably 45 nm or less. Here, the half-width refers to the peak width (nm) at half the intensity of the peak intensity at the wavelength of the peak top. Any combination of the individual upper and lower limits of the wavelength ranges described here is assumed. Any combination of the individual upper and lower limits of the half-widths described here is assumed. The peak intensity is The emission spectrum of the backlight light source can be measured, for example, using a multichannel spectrometer PMA-12 manufactured by Hamamatsu Photonics.

[0025] In any of the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, or 600 nm or more and less than 780 nm, When a peak is present, it is considered as follows. When the multiple peaks are independent peaks, it is preferable that the half-width of the peak with the highest peak intensity is in the above range. Furthermore, it is more preferable that the half-width of other peaks having an intensity of 70% or more of the highest peak intensity is in the above range. For an independent peak having a shape in which multiple peaks overlap, if the half-width of the peak with the highest peak intensity among the multiple peaks can be measured as it is, the half-width is used. Here, an independent peak is one that has an intensity region that is 1 / 2 the peak intensity on both the short wavelength side and the long wavelength side of the peak. In other words, when multiple peaks overlap and each peak does not have an intensity region that is 1 / 2 the peak intensity, the multiple peaks are regarded as a single peak as a whole. For such a single peak having a shape in which multiple peaks overlap, the half-width is the width (nm) of the peak at 1 / 2 the intensity of the highest peak intensity among them. The point with the highest peak intensity among the multiple peaks is the peak top. When multiple peaks exist within a single wavelength region, the half-widths are indicated by double-headed arrows in FIGS.

[0026] In Figure 1, peaks A and B each have a point on the short wavelength side and long wavelength side where the peak intensity is half that of the peak. Therefore, peaks A and B are independent peaks. In the case of Figure 1, the half-width can be evaluated based on the width of the double-headed arrow of peak A, which has the highest peak intensity.

[0027] In FIG. 2, peak A has points on the short wavelength side and long wavelength side where the peak intensity is 1 / 2, but peak B does not have a point on the long wavelength side where the peak intensity is 1 / 2. Therefore, peaks A and B are regarded as one independent peak. For an independent peak having a shape in which multiple peaks overlap, if the half-width of the peak with the highest peak intensity among the multiple peaks can be measured as it is, the half-width is regarded as the half-width of the independent peak. Therefore, in the case of FIG. 2, the half-width of the peak is the width of the double-headed arrow.

[0028] In Figure 3, there is no point on the short wavelength side where the peak intensity is half that of the peak A. Peak A and peak B do not have a point on the long wavelength side where the intensity is half of the peak intensity. Therefore, in Figure 3, similar to Figure 2, peak A and peak B are regarded as a single independent peak, and the half-width is the width indicated by the double-headed arrow.

[0029] In Figure 4, peak A has points on the short wavelength side and long wavelength side where the peak intensity is 1 / 2, but peak B does not have a point on the long wavelength side where the peak intensity is 1 / 2. Therefore, peaks A and B are regarded as one independent peak. For an independent peak having a shape in which multiple peaks overlap, if the half-width of the peak with the highest peak intensity among the multiple peaks can be measured as it is, that half-width is used. Therefore, in the case of Figure 4, the half-width is the width indicated by the double-headed arrow.

[0030] 1 to 4 show an example of a wavelength region of 400 nm or more and less than 495 nm, but the same concept is also applicable to other wavelength regions.

[0031] Among the multiple peaks, the peak with the highest peak intensity is determined as the peak top. In addition, it is preferable that the peaks having the highest peak intensity in the wavelength region of 400 nm to less than 495 nm, the wavelength region of 495 nm to less than 600 nm, or the wavelength region of 600 nm to 780 nm are independent of the peaks in other wavelength regions. In particular, it is preferable in terms of color vividness that there is a region in the wavelength region between the peak having the highest peak intensity in the wavelength region of 495 nm to less than 600 nm and the peak having the highest peak intensity in the wavelength region of 600 nm to 780 nm, in which the intensity is 1 / 3 or less of the peak intensity of the peak having the highest peak intensity in the wavelength region of 600 nm to 780 nm.

[0032] The emission spectrum of the backlight light source can be measured using a spectrometer such as the multichannel spectrometer PMA-12 manufactured by Hamamatsu Photonics.

[0033] As a result of intensive research, the present inventors have found that in a liquid crystal display device having a backlight source with a relatively narrow half-width of each peak of the emission spectrum, such as a light source that emits excitation light and a backlight source that contains quantum dots, by using a polyester film having an antireflection layer and / or a low reflection layer and a specific retardation as a polarizer protective film, it is possible to provide a liquid crystal display device in which rainbow spots are suppressed, and a polarizing plate useful for providing the same. The mechanism by which the occurrence of rainbow-like color spots is suppressed by the above-mentioned embodiment is considered to be as follows.

[0034] When an oriented polyester film is disposed on one side of a polarizer, the linearly polarized light emitted from the backlight unit or the polarizer changes its polarization state when passing through the polyester film. One of the factors that may cause the change in polarization state is the refractive index difference at the interface between the air layer and the oriented polyester film, or the refractive index difference at the interface between the polarizer and the oriented polyester film. When the linearly polarized light that is incident on the oriented polyester film passes through each interface, a part of the light is reflected due to the refractive index difference between the interfaces. At this time, the polarization state of both the emitted light and the reflected light changes, which is considered to be one of the factors that cause rainbow-like color spots. For this reason, it is considered that by providing an anti-reflection layer or a low-reflection layer on the surface of the oriented polyester film to reduce surface reflection, the reflection at the interface between the air layer and the oriented polyester film is suppressed, and rainbow-like color spots are suppressed.

[0035] As described above, by combining a backlight source having a relatively narrow half-width of each peak in the emission spectrum, such as a light source that emits excitation light and a backlight source that includes quantum dots, with a polarizing plate that uses a polyester film as a polarizer protective film, it is possible to suppress rainbow color spots and achieve good visibility.

[0036] The polarizing plate preferably has a polarizer protective film made of a polyester film laminated on at least one surface of the polarizer. The polyester film used for the polarizer protective film preferably has a retardation of 1500 to 30000 nm. If the retardation is within the above range, it is preferable because it tends to be easier to reduce rainbow spots. The preferred lower limit of the retardation is 3000 nm, the next preferred lower limit is 3500 nm, the more preferred lower limit is 4000 nm, the even more preferred lower limit is 6000 nm, and the even more preferred lower limit is 8000 nm. The preferred upper limit is 30000 nm, and polyester films having retardations greater than this tend to be significantly thicker and less easy to handle as industrial materials. In this specification, retardation means in-plane retardation unless otherwise indicated.

[0037] The retardation can be obtained by measuring the refractive index in two axial directions and the thickness, or by using a commercially available automatic birefringence measuring device such as KOBRA-21ADH (Oji Scientific Instruments Co., Ltd.). The refractive index can be obtained by an Abbe refractometer (measurement wavelength 589 nm).

[0038] The ratio (Re / Rth) of the retardation (Re: in-plane retardation) of the polyester film to the retardation in the thickness direction (Rth) is preferably 0.2 or more, preferably 0.3 or more, preferably 0.4 or more, preferably 0.5 or more, more preferably 0.5 or more, and even more preferably 0.6 or more. The larger the ratio (Re / Rth) of the retardation to the retardation in the thickness direction, the more isotropic the birefringence action becomes, and the less likely it is that rainbow-like color spots will occur depending on the observation angle. In a completely uniaxial (symmetrical with one axis) film, the ratio (Re / Rth) of the retardation to the retardation in the thickness direction is 2.0. The upper limit of the ratio (Re / Rth) of the retardation to the thickness retardation is preferably 2.0. The thickness retardation means the average of the retardations obtained by multiplying the two birefringences ΔNxz and ΔNyz by the film thickness d when the film is viewed from the thickness cross section.

[0039] From the viewpoint of suppressing rainbow-like color spots, the NZ coefficient of the polyester film is preferably 2.5 or less, more preferably 2.0 or less, even more preferably 1.8 or less, and even more preferably 1.6 or less. In a completely uniaxial (uniaxially symmetric) film, the NZ coefficient is 1.0, so the lower limit of the NZ coefficient is 1.0. However, it should be noted that as the film approaches a completely uniaxial (uniaxially symmetric) film, the mechanical strength in the direction perpendicular to the orientation direction tends to decrease significantly.

[0040] The NZ coefficient is expressed by |Ny-Nz| / |Ny-Nx|, where Ny is the refractive index in the slow axis direction, Nx is the refractive index in the direction perpendicular to the slow axis (the refractive index in the fast axis direction), and Nz is the refractive index in the thickness direction. The orientation axis of the film is determined using a molecular orientation meter (MOA-6004 type molecular orientation meter manufactured by Oji Measuring Instruments Co., Ltd.), and the biaxial refractive indexes (Ny, Nx, where Ny>Nx) in the orientation axis direction and the direction perpendicular to it, and the refractive index (Nz) in the thickness direction are determined using an Abbe refractometer (NAR-4T manufactured by Atago Co., Ltd., measurement wavelength 589 nm). The NZ coefficient can be determined by substituting the values ​​thus determined into |Ny-Nz| / |Ny-Nx|.

[0041] In order to further suppress rainbow-like color spots, the Ny-Nx value of the polyester film is preferably 0.05 or more, more preferably 0.07 or more, even more preferably 0.08 or more, still more preferably 0.09 or more, and most preferably 0.1 or more. There is no particular upper limit, but in the case of a polyethylene terephthalate film, the upper limit is preferably about 1.5.

[0042] In a more preferred embodiment of the present invention, the refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer constituting the polarizing plate is preferably in the range of 1.53 to 1.62. This makes it possible to suppress reflection at the interface between the polarizer and the polyester film and suppress rainbow-like color spots. If the refractive index exceeds 1.62, rainbow-like color spots may occur when observed from an oblique direction. The refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer is preferably 1.61 or less, more preferably 1.60 or less, even more preferably 1.59 or less, and even more preferably 1.58 or less.

[0043] On the other hand, the lower limit of the refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer is 1.53. If the refractive index is less than 1.53, the crystallization of the polyester film becomes insufficient, and the properties obtained by stretching, such as dimensional stability, mechanical strength, and chemical resistance, become insufficient, which is not preferable. The refractive index is preferably 1.56 or more, more preferably 1.57 or more. Any range combining the upper and lower limits of the refractive index described above is assumed.

[0044] In order to set the refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer to a range of 1.53 to 1.62, it is preferable that the transmission axis of the polarizer and the fast axis (perpendicular to the slow axis) of the polyester film are parallel to each other in the polarizing plate. The refractive index of the polyester film in the fast axis direction, which is perpendicular to the slow axis, can be adjusted to a low value of about 1.53 to 1.62 by a stretching treatment in the film-forming process described later. By making the fast axis direction of the polyester film parallel to the transmission axis direction of the polarizer, the refractive index of the polyester film in the direction parallel to the transmission axis direction of the polarizer can be set to 1.53 to 1.62. Here, being parallel means that the angle between the transmission axis of the polarizer and the fast axis of the polarizer protective film is -15° to 15°, preferably -10° to 10°, more preferably -5° to 5°, even more preferably -3° to 3°, still more preferably -2° to 2°, and even more preferably -1° to 1°. In a preferred embodiment, "parallel" means "substantially parallel." Here, "substantially parallel" means that the transmission axis and the fast axis are parallel to an extent that allows for the misalignment that inevitably occurs when the polarizer and the protective film are bonded together. The direction of the slow axis can be measured using a molecular orientation meter (e.g., MOA-6004 type molecular orientation meter manufactured by Oji Scientific Instruments Co., Ltd.).

[0045] In other words, the refractive index of the polyester film in the fast axis direction is preferably 1.53 or more and 1.62 or less. By laminating the polyester film so that the transmission axis of the polarizer and the fast axis of the polyester film are approximately parallel to each other, the refractive index of the polyester film in the direction parallel to the transmission axis of the polarizer can be made 1.53 or more and 1.62 or less.

[0046] The above-mentioned polyester film-made polarizer protective film can be used for polarizing plates on both the incident light side (light source side) and the outgoing light side (viewing side). In a polarizing plate arranged on the incident light side, the above-mentioned polyester film-made polarizer protective film may be arranged on the incident light side, on the liquid crystal cell side, or on both sides, with the polarizer as the starting point, but is preferably arranged on at least the incident light side. In a polarizing plate arranged on the outgoing light side, the above-mentioned polyester film-made polarizer protective film may be arranged on the liquid crystal side, on the outgoing light side, or on both sides, with the polarizer as the starting point, but is preferably arranged on at least the outgoing light side.

[0047] The polyester used in the polyester film may be polyethylene terephthalate or polyethylene naphthalate, but may contain other copolymerization components. These resins are excellent in transparency and thermal and mechanical properties, and retardation can be easily controlled by stretching. In particular, polyethylene terephthalate is the most suitable material because it has a large inherent birefringence, and the refractive index in the fast axis direction (perpendicular to the slow axis direction) can be kept low by stretching the film, and a large retardation can be obtained relatively easily even if the film is thin.

[0048] In addition, in order to suppress deterioration of optically functional dyes such as iodine dyes, the polyester film desirably has a light transmittance of 20% or less at a wavelength of 380 nm. The light transmittance of 380 nm is more preferably 15% or less, even more preferably 10% or less, and particularly preferably 5% or less. If the light transmittance is 20% or less, deterioration of the optically functional dye caused by ultraviolet rays can be suppressed. The transmittance is measured perpendicular to the plane of the film, and can be measured using a spectrophotometer (e.g., Hitachi U-3500 type).

[0049] In order to make the transmittance of the polyester film at a wavelength of 380 nm 20% or less, it is desirable to appropriately adjust the type and concentration of the ultraviolet absorber and the thickness of the film. The ultraviolet absorber used in the present invention is a known substance. Examples of ultraviolet absorbers include organic ultraviolet absorbers and inorganic ultraviolet absorbers, and from the viewpoint of transparency, organic ultraviolet absorbers are preferred. Examples of organic ultraviolet absorbers include benzotriazole-based, benzophenone-based, cyclic imino ester-based, and combinations thereof, but are not particularly limited as long as they are within the range of absorbance specified in the present invention. However, from the viewpoint of durability, benzotriazole-based and cyclic imino ester-based are particularly preferred. When two or more types of ultraviolet absorbers are used in combination, ultraviolet rays of different wavelengths can be absorbed simultaneously, so that the ultraviolet absorption effect can be further improved.

[0050] Benzophenone-based ultraviolet absorbers, benzotriazole-based ultraviolet absorbers, and acrylonitrile-based ultraviolet absorbers include, for example, 2-[2'-hydroxy-5'-(methacryloyloxymethyl)phenyl]-2H-benzotriazole, 2-[2'-hydroxy-5'-(methacryloyloxyethyl)phenyl]-2H-benzotriazole, 2-[2' -Hydroxy-5'-(methacryloyloxypropyl)phenyl]-2H-benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, 2,4-di-tert-butyl-6-(5-chlorobenzotriazol-2-yl)phenol, 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(5-chloro(2H)-benzotriazol-2-yl)-4-methyl-6-(tert-butyl)phenol Examples of the cyclic imino ester ultraviolet absorbers include 2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one), 2-methyl-3,1-benzoxazin-4-one, 2-butyl-3,1-benzoxazin-4-one, 2-phenyl-3,1-benzoxazin-4-one, etc. However, the present invention is not limited to these.

[0051] In addition, in addition to the ultraviolet absorber, it is also a preferred embodiment to contain various additives other than the catalyst within a range that does not impair the effects of the present invention. Examples of additives include inorganic particles, heat-resistant polymer particles, alkali metal compounds, alkaline earth metal compounds, phosphorus compounds, antistatic agents, light-resistant agents, flame retardants, heat stabilizers, antioxidants, gelling inhibitors, surfactants, etc. In addition, in order to achieve high transparency, it is also preferable that the polyester film does not substantially contain particles. "Substantially does not contain particles" means, for example, in the case of inorganic particles, a content that is 50 ppm or less, preferably 10 ppm or less, and particularly preferably below the detection limit when inorganic elements are quantified by fluorescent X-ray analysis.

[0052] It is preferable to provide an antireflection layer and / or a low reflection layer on at least one surface of the polyester film, which is a polarizer protective film. The surface reflectance of the antireflection layer is preferably 2.0% or less. If it exceeds 2.0%, rainbow-like color spots are easily visible. The surface reflectance of the antireflection layer is more preferably 1.6% or less, even more preferably 1.2% or less, and particularly preferably 1.0% or less. The lower limit of the surface reflectance of the antireflection layer is not particularly limited, but is, for example, 0.01%. The reflectance can be measured by any method, and for example, a spectrophotometer (Shimadzu Corporation, UV-3150) can be used to measure the light reflectance at a wavelength of 550 nm from the surface on the antireflection layer side.

[0053] The anti-reflection layer may be a single layer or a multilayer. In the case of a single layer, the anti-reflection effect can be obtained by forming the low refractive index layer made of a material with a lower refractive index than the polyester film so that the thickness is 1 / 4 of the light wavelength or an odd multiple of that. In the case of a multilayer anti-reflection layer, the anti-reflection effect can be obtained by alternately forming two or more low refractive index layers and high refractive index layers and laminating them while appropriately controlling the thickness of each layer. In addition, if necessary, a hard coat layer can be laminated between the anti-reflection layers, and an anti-fouling layer can be formed on the hard coat layer.

[0054] The anti-reflection layer may be one that utilizes a moth-eye structure. The moth-eye structure is an uneven structure formed on the surface with a pitch smaller than the wavelength, and this structure makes it possible to change the sudden and discontinuous change in refractive index at the boundary with air into a continuous and gradual change in refractive index. Thus, by forming the moth-eye structure on the surface, light reflection on the surface of the film is reduced. The formation of an anti-reflection layer that utilizes a moth-eye structure can be carried out by referring to, for example, JP-T 2001-517319.

[0055] Examples of methods for forming an anti-reflection layer include a dry coating method in which an anti-reflection layer is formed on the surface of a substrate (polyester film) by vapor deposition or sputtering, a wet coating method in which an anti-reflection coating liquid is applied to the surface of the substrate and then dried to form an anti-reflection layer, and a combination method in which both of these methods are used in combination. There are no particular limitations on the material as long as it satisfies the above characteristics.

[0056] The low reflection layer may be a known one. For example, it may be formed by laminating at least one or more layers of a metal or oxide thin film by vapor deposition or sputtering, or by coating one or more layers of an organic thin film. As the low reflection layer, a layer of an organic thin film having a lower refractive index than a polyester film or a hard coat layer laminated on a polyester film is preferably used. The surface reflectance of the low reflection layer is preferably less than 5%, more preferably 4% or less, and even more preferably 3% or less. The lower limit is preferably about 0.8% to 1.0%.

[0057] The anti-reflection layer and / or the low-reflection layer may further be provided with an anti-glare function. This can further suppress iridescence. That is, the combination of an anti-reflection layer and an anti-glare layer, the combination of a low-reflection layer and an anti-glare layer, or the combination of an anti-reflection layer, a low-reflection layer and an anti-glare layer may be used. The combination of a low-reflection layer and an anti-glare layer is particularly preferred. As the anti-glare layer, a known anti-glare layer can be used. For example, from the viewpoint of suppressing the surface reflection of the film, it is preferred to laminate an anti-glare layer on a polyester film, and then laminate an anti-reflection layer or a low-reflection layer on the anti-glare layer.

[0058] When providing an anti-reflection layer or a low reflection layer, it is preferable that the polyester film has an easy-adhesion layer on its surface. In this case, from the viewpoint of suppressing interference caused by reflected light, it is preferable to adjust the refractive index of the easy-adhesion layer so that it is close to the geometric mean of the refractive index of the anti-reflection layer and the refractive index of the polyester film. The refractive index of the easy-adhesion layer can be adjusted by a known method, and can be easily adjusted by, for example, adding titanium, germanium, or other metal species to the binder resin.

[0059] The polyester film may be subjected to a corona treatment, a coating treatment and / or a flame treatment in order to improve the adhesion to the polarizer.

[0060] In the present invention, in order to improve the adhesion to the polarizer, it is preferable that at least one surface of the film of the present invention has an easy-adhesion layer mainly composed of at least one of polyester resin, polyurethane resin, and polyacrylic resin. Here, the "main component" refers to a component that accounts for 50 mass% or more of the solid components constituting the easy-adhesion layer. The coating liquid used to form the easy-adhesion layer of the present invention is preferably an aqueous coating liquid containing at least one of water-soluble or water-dispersible copolymer polyester resin, acrylic resin, and polyurethane resin. Examples of these coating liquids include water-soluble or water-dispersible copolymer polyester resin solutions, acrylic resin solutions, and polyurethane resin solutions disclosed in Japanese Patent No. 3567927, Japanese Patent No. 3589232, Japanese Patent No. 3589233, Japanese Patent No. 3900191, and Japanese Patent No. 4150982, etc.

[0061] The easy-adhesion layer can be obtained by applying the coating liquid to one or both sides of a uniaxially stretched film in the longitudinal direction, drying the film at 100 to 150° C., and then stretching the film in the transverse direction. The final coating amount of the easy-adhesion layer is 0.05 to 0.20 g / m 2 It is preferable to control the coating amount to 0.05 g / m 2 If the coating amount is less than 0.20 g / m, the adhesion to the obtained polarizer may be insufficient. 2When the easy-adhesion layer is provided on both sides of the polyester film, the coating amounts of the easy-adhesion layers on both sides may be the same or different, and each can be independently set within the above range.

[0062] It is preferable to add particles to the adhesive layer to give it slipperiness. It is preferable to use particles having an average particle size of 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles tend to fall off from the coating layer. Examples of particles to be contained in the adhesive layer include thiophene. Examples of the inorganic particles include tungsten, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more of them may be added in combination.

[0063] The coating liquid can be applied by any known method, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.

[0064] The average particle size of the above particles is measured by the following method: Particles are photographed with a scanning electron microscope (SEM), and the maximum diameters (the distance between the two most distant points) of 300 to 500 particles are measured at a magnification such that the size of the smallest particle is 2 to 5 mm, and the average value is taken as the average particle size.

[0065] The polyester film used as the polarizer protective film can be produced according to a general method for producing a polyester film, for example, by melting a polyester resin, extruding the non-oriented polyester into a sheet, stretching the sheet in the longitudinal direction at a temperature equal to or higher than the glass transition temperature by utilizing the speed difference between rolls, stretching the sheet in the transverse direction by a tenter, and then subjecting the sheet to a heat treatment.

[0066] The polyester film used in the present invention may be either a uniaxially oriented film or a biaxially oriented film.

[0067] Specifically, the film-forming conditions of the polyester film are as follows: the longitudinal stretching temperature and the transverse stretching temperature are preferably 80 to 130°C, and particularly preferably 90 to 120°C. In order to orient the film so that the slow axis is in the TD direction, the longitudinal stretching ratio is preferably 1.0 to 3.5 times, and particularly preferably 1.0 to 3.0 times. In addition, the transverse stretching ratio is preferably 2.5 to 6.0 times, and particularly preferably 3.0 to 5.5 times. In order to orient the film so that the slow axis is in the MD direction, the longitudinal stretching ratio is preferably 2.5 to 6.0 times, and particularly preferably 3.0 to 5.5 times. In addition, the transverse stretching ratio is preferably 1.0 to 3.5 times, and particularly preferably 1.0 to 3.0 times.

[0068] Setting the stretching temperature low is also a preferable measure for lowering the refractive index in the fast axis direction of the polyester film and increasing the retardation. In the subsequent heat treatment, the treatment temperature is preferably 100 to 250°C, particularly preferably 180 to 245°C.

[0069] In order to suppress the fluctuation of the retardation, it is preferable that the thickness unevenness of the film is small. Since the stretching temperature and the stretching ratio have a large effect on the thickness unevenness of the film, it is preferable to optimize the film-forming conditions from the viewpoint of reducing the thickness unevenness. In particular, when the longitudinal stretching ratio is reduced in order to increase the retardation, the longitudinal thickness unevenness may become large. Since the longitudinal thickness unevenness becomes very bad in a certain range of the stretching ratio, it is preferable to set the film-forming conditions outside this range.

[0070] The thickness unevenness of the polyester film is preferably 5.0% or less, more preferably 4.5% or less, even more preferably 4.0% or less, and particularly preferably 3.0% or less. The thickness unevenness of the film can be measured as follows. A tape-shaped film sample (3 m) is taken and measured using an electronic measuring device manufactured by Seiko EM Co., Ltd. Using a micrometer, Millitron 1240, the thickness is measured at 100 points at 1 cm intervals. The maximum thickness (dmax), minimum thickness (dmin), and average thickness (d) are calculated from the measured values ​​and calculated using the following formula: The thickness unevenness (%) is calculated by the following formula: It is preferable to carry out the measurement three times and calculate the average value. Thickness unevenness (%) = ((dmax-dmin) / d) x 100 As described above, in order to control the retardation of the polyester film within a specific range, it can be performed by appropriately setting the stretching ratio, stretching temperature, and film thickness. For example, the higher the stretching ratio, the lower the stretching temperature, and the thicker the film, the easier it is to obtain a high retardation. Conversely, the lower the stretching ratio, the higher the stretching temperature, and the thinner the film, the easier it is to obtain a low retardation. However, if the film thickness is increased, the thickness direction phase difference tends to increase. Therefore, it is desirable to appropriately set the film thickness within the range described below. In addition to controlling the retardation, it is preferable to set the final film formation conditions taking into account the physical properties required for processing.

[0071] The thickness of the polyester film is arbitrary, but is preferably in the range of 15 to 300 μm, and more preferably in the range of 15 to 200 μm. In principle, it is possible to obtain a retardation of 1500 nm or more even with a film having a thickness of less than 15 μm. However, in that case, the anisotropy of the mechanical properties of the film becomes significant, and it becomes easy to cause tears, breaks, etc., and the practicality as an industrial material is significantly reduced. A particularly preferable lower limit of the thickness is 25 μm. On the other hand, if the upper limit of the thickness of the polarizer protective film exceeds 300 μm, the thickness of the polarizing plate becomes too thick, which is not preferable. From the viewpoint of practicality as a polarizer protective film, the upper limit of the thickness is preferably 200 μm. A particularly preferable upper limit of the thickness is 100 μm, which is about the same as that of a general TAC film. In order to control the retardation within the range of the present invention even in the above thickness range, the polyester used as the film substrate is preferably polyethylene terephthalate.

[0072] As a method for incorporating an ultraviolet absorber into a polyester film, a combination of known methods can be adopted. For example, the ultraviolet absorber can be incorporated by a method in which a dried ultraviolet absorber is blended in advance with a polymer raw material using a kneading extruder to prepare a master batch, and then a predetermined master batch is mixed with the polymer raw material during film formation.

[0073] In this case, the concentration of the ultraviolet absorber in the master batch is preferably 5 to 30% by mass in order to disperse the ultraviolet absorber uniformly and to compound economically. The conditions for preparing the master batch are preferably a kneading extruder, and the extrusion temperature is from the melting point of the polyester raw material to 290°C or less for 1 to 15 minutes. If the temperature is 290°C or higher, the weight loss of the ultraviolet absorber is large, and the viscosity of the master batch is significantly reduced. If the extrusion temperature is 1 minute or less, it is difficult to mix the ultraviolet absorber uniformly. At this time, a stabilizer, a color tone adjuster, and / or an antistatic agent may be added as necessary.

[0074] It is preferable that the polyester film has a multi-layer structure of at least three layers, and an ultraviolet absorber is added to the intermediate layer of the film. A three-layer film containing an ultraviolet absorber in the intermediate layer can be specifically produced as follows. A polyester pellet alone for the outer layer, and a master batch containing an ultraviolet absorber and a polyester pellet for the intermediate layer are mixed in a predetermined ratio, dried, and then fed to a known melt lamination extruder, extruded into a sheet from a slit-shaped die, and cooled and solidified on a casting roll to produce an unstretched film. That is, using two or more extruders, a three-layer manifold or a merging block (for example, a merging block having a square merging portion), the film layers constituting both outer layers and the film layer constituting the intermediate layer are laminated, the three-layer sheet is extruded from the die, and cooled on a casting roll to produce an unstretched film. In the present invention, in order to remove foreign matter contained in the raw polyester that causes optical defects, it is preferable to perform high-precision filtration during melt extrusion. Filter particle size of filter material used for high-precision filtration of molten resin (initial filtration efficiency 95%) If the filtering particle size of the filter medium exceeds 15 μm, the removal of foreign matter of 20 μm or more tends to be insufficient. EXAMPLES

[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples, and can be practiced with appropriate modifications within the scope of the invention, all of which are included in the technical scope of the present invention. The methods for evaluating physical properties in the following examples are as follows.

[0076] (1) Refractive index of polyester film The slow axis direction of the film was determined using a molecular orientation meter (MOA-6004 molecular orientation meter, manufactured by Oji Measurement Instruments Co., Ltd.), and a 4 cm x 2 cm rectangle was cut out so that the slow axis direction was parallel to the long side to prepare a measurement sample. The refractive indexes of the two orthogonal axes (refractive index in the slow axis direction: Ny, fast axis (refractive index in the direction perpendicular to the slow axis direction): Nx) and the refractive index in the thickness direction (Nz) of this sample were determined using an Abbe refractometer (NAR-4T, manufactured by Atago Co., Ltd., measurement wavelength 589 nm).

[0077] (2) Retardation (Re) Retardation is a parameter defined by the product (ΔNxy×d) of the refractive index anisotropy of two orthogonal axes on a film (ΔNxy=|Nx-Ny|) and the film thickness d (nm), and is a measure of optical isotropy and anisotropy. The biaxial refractive index anisotropy (ΔNxy) was obtained by the method (1) above, and the absolute value of the refractive index difference between the two axes (|Nx-Ny|) was calculated as the refractive index anisotropy (ΔNxy). The film thickness d (nm) was measured using an electric micrometer (Militron 1245D, manufactured by Fine Leaf Co., Ltd.) and converted to nm. The retardation (Re) was calculated from the product (ΔNxy×d) of the refractive index anisotropy (ΔNxy) and the film thickness d (nm).

[0078] (3) Thickness retardation (Rth) The thickness retardation is a parameter that indicates the average retardation obtained by multiplying the two birefringences ΔNxz (=|Nx-Nz|) and ΔNyz (=|Ny-Nz|) when viewed from the cross section of the film thickness direction by the film thickness d. Nx, Ny, Nz and the film thickness d (nm) were obtained in the same manner as in the retardation measurement, and the average value of (ΔNxz×d) and (ΔNyz×d) was calculated to obtain the thickness retardation (Rth).

[0079] (4) NZ coefficient The values ​​of Ny, Nx, and Nz obtained in (1) above were substituted into the formula (NZ=|Ny-Nz| / |Ny-Nx|) to obtain the value of the NZ coefficient.

[0080] (5) Measurement of the emission spectrum of the backlight light source The liquid crystal display device used in each example was a BRAVIA KDL-40W920A manufactured by SONY (a liquid crystal display device having a light source that emits excitation light and a backlight light source containing quantum dots). When the emission spectrum of the backlight light source of this liquid crystal display device was measured using a multichannel spectrometer PMA-12 manufactured by Hamamatsu Photonics, an emission spectrum having peak tops near 450 nm, 528 nm, and 630 nm was observed, and the half-width of each peak top was 17 nm to 34 nm. The exposure time during the spectrum measurement was 20 msec.

[0081] (6)Reflectance Using a spectrophotometer (Shimadzu Corporation, UV-3150), 5-degree reflection at a wavelength of 550 nm was performed. The reflectance was measured from the surface on the antireflection layer side (or low reflection layer side). The surface of the polyester film opposite to the antireflection layer (or low reflection layer) was coated with black marker and then black vinyl tape (Kyowa Vinyl Tape HF-737, width 50 mm) was attached thereto.

[0082] (7) Iridescence observation The liquid crystal display device obtained in each example was visually observed in a dark place from the front and from an oblique direction, and the occurrence of rainbow spots was judged as follows: Here, the oblique direction means a range of 30 degrees to 60 degrees from the normal direction of the screen of the liquid crystal display device.

[0083] ○: No rainbow spots observed △: Slight rainbow spots observed ×: Iridescence observed ××: Iridescence is significantly observed

[0084] (Production Example 1-Polyester A) When the temperature of the esterification reactor reached 200°C, 86.4 parts by mass of terephthalic acid and 64.6 parts by mass of ethylene glycol were charged, and 0.017 parts by mass of antimony trioxide, 0.064 parts by mass of magnesium acetate tetrahydrate, and 0.16 parts by mass of triethylamine were charged as catalysts while stirring. Next, the temperature was increased under pressure and a pressure esterification reaction was carried out under conditions of a gauge pressure of 0.34 MPa and 240°C, after which the esterification reactor was returned to normal pressure and 0.014 parts by mass of phosphoric acid was added. Further, the temperature was increased to 260°C over 15 minutes, and 0.012 parts by mass of trimethyl phosphate was added. Next, after 15 minutes, a dispersion treatment was carried out using a high-pressure disperser, and after 15 minutes, the obtained esterification reaction product was transferred to a polycondensation reactor and a polycondensation reaction was carried out under reduced pressure at 280°C.

[0085] After the polycondensation reaction was completed, the mixture was filtered using a Naslon filter with a 95% cut diameter of 5 μm, extruded from a nozzle in the form of a strand, cooled and solidified using cooling water that had been previously filtered (pore diameter: 1 μm or less), and cut into pellets. The intrinsic viscosity of the resulting polyethylene terephthalate resin (A) was 0.62 dl / g, and it contained substantially no inert particles or internally precipitated particles. (Hereinafter, this will be abbreviated as PET (A)).

[0086] (Production Example 2 - Polyester B) 10 parts by mass of dried ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) and 90 parts by mass of particle-free PET (A) (intrinsic viscosity 0.62 dl / g) were mixed and kneaded using an extruder to obtain polyethylene terephthalate resin (B) containing an ultraviolet absorber (hereinafter referred to as PET (B)).

[0087] (Production Example 3 - Preparation of Adhesion Modifier Coating Solution) By carrying out an ester exchange reaction and a polycondensation reaction by a conventional method, a water-dispersible sulfonate metal base-containing copolymerized polyester resin was prepared, which has a composition of 46 mol% terephthalic acid, 46 mol% isophthalic acid, and 8 mol% sodium 5-sulfonatoisophthalate as dicarboxylic acid components (relative to the total dicarboxylic acid components), 50 mol% ethylene glycol, and 50 mol% neopentyl glycol as glycol components (relative to the total glycol components). Next, 51.4 parts by mass of water, 38 parts by mass of isopropyl alcohol, 5 parts by mass of n-butyl cellosolve, and 0.06 parts by mass of a nonionic surfactant were mixed, heated and stirred, and when the temperature reached 77°C, 5 parts by mass of the water-dispersible sulfonate metal base-containing copolymerized polyester resin was added, and the mixture was stirred until no resin lumps remained, and then the resin aqueous dispersion was cooled to room temperature to obtain a uniform water-dispersible copolymerized polyester resin liquid with a solid content concentration of 5.0% by mass. Furthermore, 3 parts by mass of aggregated silica particles (manufactured by Fuji Silysia Co., Ltd., Silica 310) were dispersed in 50 parts by mass of water. Thereafter, 0.54 parts by mass of the aqueous dispersion of Cylysia 310 was added to 99.46 parts by mass of the water-dispersible copolymerized polyester resin solution, and 20 parts by mass of water was added with stirring to obtain an adhesion-modifying coating solution.

[0088] (Production Example 4 - Preparation of high refractive index coating agent) 80 parts of methyl methacrylate, 20 parts of methacrylic acid, 1 part of azoisobutyronitrile, and 200 parts of isopropyl alcohol were charged into a reaction vessel and reacted at 80° C. for 7 hours under a nitrogen atmosphere to obtain an isopropyl alcohol solution of a polymer having a weight average molecular weight of 30,000. The obtained polymer solution was further diluted with isopropyl alcohol to a solid content of 5% to obtain an acrylic resin solution B. Next, the obtained acrylic resin solution B was mixed with the following components to obtain a coating liquid for forming a high refractive index layer.

[0089] Acrylic resin solution B 5 parts by weight Bisphenol A diglycidyl ether 0.25 parts by weight Titanium oxide particles with an average particle size of 20 nm: 0.5 parts by weight Triphenylphosphine 0.05 parts by mass 14.25 parts by weight of isopropyl alcohol

[0090] (Production Example 5 - Preparation of low refractive index coating agent) 2,2,2-trifluoroethyl acrylate (45 parts by mass), perfluorooctylethyl acrylate (45 parts by mass), acrylic acid (10 parts by mass), azoisobutyronitrile (1.5 parts by mass), and methyl ethyl ketone (200 parts by mass) were charged into a reaction vessel and reacted at 80°C for 7 hours under a nitrogen atmosphere to obtain a methyl ethyl ketone solution of a polymer having a weight average molecular weight of 20.000. The obtained polymer solution was diluted with methyl ethyl ketone to a solid content concentration of 5% by mass to obtain a fluoropolymer solution C. The obtained fluoropolymer solution C was mixed as follows to obtain a coating liquid for forming a low refractive index layer.

[0091] Fluoropolymer solution C 4 4 parts by mass 1,10-bis(2,3-epoxypropoxy) - 2,2,3,3,4,4,5,5,6,6,7,7 , 8,8,9,9 - Hexadecafluorodecane (Kyoeisha Chemical, Fluorite FE-16) 1 part by mass Triphenylphosphine 0.1 parts by mass Methyl ethyl ketone 19 parts by weight

[0092] (Production Example 6 - Preparation of Antiglare Layer Coating Agent-1) An antiglare layer-forming coating solution was obtained by adding the solid components of the unsaturated double bond-containing acrylic copolymer CYCLOMER P ACA-Z250 (manufactured by Daicel Chemical Industries, Ltd.) (49 parts by mass), cellulose acetate propionate CAP482-20 (number average molecular weight 75,000) (manufactured by Eastman Chemical Co., Ltd.) (3 parts by mass), acrylic monomer AYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.) (49 parts by mass), acrylic-styrene copolymer (average particle size 4.0 μm) (manufactured by Sekisui Chemical Co., Ltd.) (2 parts by mass), and Irgacure 184 (manufactured by BASF) (10 parts by mass) to a mixed solvent of methyl ethyl ketone:1-butanol = 3:1 so as to make the solid component amount 35 mass%.

[0093] (Production Example 7 - Preparation of Antiglare Layer Coating Agent-2) Unsaturated double bond-containing acrylic copolymer Cyclomer P ACA-Z250 (manufactured by Daicel Chemical Industries, Ltd.) (49 parts by mass), cellulose acetate propionate CAP482-0.5 (number average molecular weight 25,000) (manufactured by Eastman Chemical Co., Ltd.) (3 parts by mass), acrylic monomer AYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.) (49 parts by mass), acrylic-styrene copolymer A coating solution for forming an antiglare layer was obtained by adding 4 parts by mass of ethylene copolymer (average particle size 4.0 μm) (manufactured by Sekisui Chemical Co., Ltd.) and 10 parts by mass of Irgacure 184 (manufactured by BASF) to a mixed solvent of methyl ethyl ketone:1-butanol = 3:1 so that the solid content was 35 mass%.

[0094] (Production Example 8 - Preparation of Antiglare Layer Coating Agent-3) The solid components of the unsaturated double bond-containing acrylic copolymer CYCLOMER P ACA-Z250 (manufactured by Daicel Chemical Industries, Ltd.) (49 parts by mass), cellulose acetate propionate CAP482-0.2 (number average molecular weight 15,000) (manufactured by Eastman Chemical Co., Ltd.) (3 parts by mass), acrylic monomer AYARAD DPHA (manufactured by Nippon Kayaku Co., Ltd.) (49 parts by mass), acrylic-styrene copolymer (average particle size 4.0 μm) (manufactured by Sekisui Chemical Co., Ltd.) (2 parts by mass), and IRGACURE 184 (manufactured by BASF) (10 parts by mass) were added to a mixed solvent of methyl ethyl ketone:1-butanol = 3:1 so as to make the solid component content 35 mass%, to obtain a coating liquid for forming an antiglare layer.

[0095] (Polarizer protection film 1) As the raw material for the intermediate layer of the base film, 90 parts by mass of PET (A) resin pellets containing no particles and 10 parts by mass of PET (B) resin pellets containing an ultraviolet absorber were dried under reduced pressure (1 Torr) at 135 ° C for 6 hours, and then fed to extruder 2 (for intermediate layer II layer), and PET (A) was dried by a conventional method and fed to extruder 1 (for outer layer I layer and outer layer III layer), respectively, and melted at 285 ° C. These two types of polymers were filtered with a stainless steel sintered filter medium (nominal filtration accuracy 10 μm particle 95% cut) and laminated in a two-type three-layer merging block, extruded into a sheet shape from a die, and then wrapped around a casting drum with a surface temperature of 30 ° C using an electrostatic casting method, cooled and solidified, and an unstretched film was made. At this time, the discharge amount of each extruder was adjusted so that the thickness ratio of I layer, II layer, and III layer was 10:80:10.

[0096] Next, the unstretched PET film was coated on both sides with a 0.08 g / m coating after drying by the reverse roll method. 2 After the adhesiveness-modifying coating liquid was applied so that the thickness became 100 μm, the coating was dried at 80° C. for 20 seconds.

[0097] The unstretched film with the coating layer formed thereon was introduced into a tenter stretching machine, and while the ends of the film were held by clips, it was introduced into a hot air zone at a temperature of 125°C and stretched 4.0 times in the width direction. Next, while maintaining the width stretched in the width direction, it was treated at a temperature of 225°C for 10 seconds, and further subjected to a relaxation treatment of 3.0% in the width direction, to obtain a uniaxially stretched PET film with a thickness of about 100 μm.

[0098] The coating liquid for forming a high refractive index layer was applied to one of the coating surfaces of the uniaxially stretched PET film and dried at 150° C. for 2 minutes to form a high refractive index layer with a thickness of 0.1 μm. The coating liquid for forming a low refractive index layer obtained by the above method was applied onto the high refractive index layer and dried at 150° C. for 2 minutes to form a low refractive index layer with a thickness of 0.1 μm, and a polarizer protective film 1 with an antireflection layer laminated thereon was obtained.

[0099] (Polarizer protection film 2) A film was produced in the same manner as in Polarizer Protective Film 1 except that the line speed was changed to change the thickness of the unstretched film, to obtain Polarizer Protective Film 2 having an antireflection layer laminated thereon and a film thickness of about 80 μm.

[0100] (Polarizer protection film 3) Polarizer protection film 1 except that the line speed was changed to change the thickness of the unstretched film. A film was formed in the same manner as in the above to obtain a polarizer protective film 3 having an antireflection layer laminated thereon and a film thickness of about 60 μm.

[0101] (Polarizer protection film 4) A film was produced in the same manner as in Polarizer Protective Film 1 except that the line speed was changed to change the thickness of the unstretched film, to obtain Polarizer Protective Film 4 having an antireflection layer laminated thereon and a film thickness of about 40 μm.

[0102] (Polarizer protection film 5) An unstretched film produced in the same manner as polarizer protective film 1 was heated to 105°C using a group of heated rolls and an infrared heater, and then stretched 3.3 times in the running direction using a group of rolls with different peripheral speeds. It was then introduced into a hot air zone at a temperature of 130°C and stretched 4.0 times in the width direction to obtain polarizer protective film 5 with a film thickness of approximately 30 μm, on which an antireflection layer was laminated in the same manner as polarizer protective film 1.

[0103] (Polarizer protection film 6) A polarizer protective film 6 having a film thickness of about 100 μm was prepared in the same manner as in the polarizer protective film 1, except that no antireflection layer was provided.

[0104] (Polarizer protection film 7) The polarizer protective film was prepared in the same manner as polarizer protective film 2, except that no anti-reflection layer was added. Anti-glare layer coating agent-1 was applied to one of the coating surfaces of the polarizer protective film so that the film thickness after curing would be 8 μm, and the film was dried in an oven at 80°C for 60 seconds. After that, it was exposed to a dose of 300 mJ / cm using an ultraviolet irradiation device (Fusion UV Systems Japan, light source H bulb).2 An antiglare layer was laminated by irradiating the film with ultraviolet light at 1000 rpm. Thereafter, an antireflection layer was laminated on the antiglare layer in the same manner as in the polarizer protective film 1, so that a polarizer protective film 7 was obtained.

[0105] (Polarizer protection film 8) A polarizer protective film was prepared in the same manner as polarizer protective film 3, except that an antireflection layer was not added, and an antiglare layer and an antireflection layer were laminated on one coating surface of the polarizer protective film in the same manner as polarizer protective film 7, to obtain polarizer protective film 8.

[0106] (Polarizer protection film 9) A polarizer protective film was prepared in the same manner as polarizer protective film 4, except that no anti-reflection layer was added. Anti-glare layer coating agent-2 was applied to one of the coating surfaces of the polarizer protective film so that the film thickness after curing would be 8 μm, and the film was dried in an oven at 80°C for 60 seconds. After that, the film was exposed to a dose of 300 mJ / cm using an ultraviolet irradiation device (Fusion UV Systems Japan, light source H bulb). 2 An antiglare layer was laminated by irradiating the film with ultraviolet light at 1000 rpm. Thereafter, an antireflection layer was laminated on the antiglare layer in the same manner as in the case of the polarizer protective film 1, so that a polarizer protective film 9 was obtained.

[0107] (Polarizer protection film 10) A polarizer protective film was prepared in the same manner as polarizer protective film 5, except that an antireflection layer was not added, and an antiglare layer was laminated on one coating surface of the polarizer protective film in the same manner as polarizer protective film 7, to obtain polarizer protective film 10 (no antireflection layer was laminated).

[0108] (Polarizer protection film 11) The polarizer protective film was prepared in the same manner as polarizer protective film 1, except that no anti-reflection layer was added. Anti-glare layer coating agent-3 was applied to one of the coating surfaces of the polarizer protective film so that the film thickness after curing would be 8 μm, and the film was dried in an oven at 80°C for 60 seconds. After that, the film was exposed to a 300 mJ / s UV irradiation device (Fusion UV Systems Japan, light source H bulb). cm 2The film was irradiated with ultraviolet light at 400 nm to obtain a polarizer protective film 11 having an antiglare layer laminated thereon.

[0109] (Polarizer protection film 12) The polarizer protective film was prepared in the same manner as polarizer protective film 2, except that no anti-reflection layer was added. Anti-glare layer coating agent-1 was applied to one of the coating surfaces of the polarizer protective film so that the film thickness after curing would be 8 μm, and the film was dried in an oven at 80°C for 60 seconds. After that, it was exposed to a dose of 300 mJ / cm using an ultraviolet irradiation device (Fusion UV Systems Japan, light source H bulb). 2 An antiglare layer was laminated by irradiating the antiglare layer with ultraviolet light at 1000 rpm. Thereafter, a low refractive index layer was laminated on the antiglare layer in the same manner as in the polarizer protective film 1. In this way, a polarizer protective film 12 in which a low reflection layer was laminated on the antiglare layer was obtained.

[0110] Using the polarizer protective films 1 to 12, liquid crystal displays were produced as described below.

[0111] Example 1 A polarizer protective film 1 was attached to one side of a polarizer made of PVA and iodine so that the transmission axis of the polarizer and the fast axis of the film were perpendicular, and a TAC film (manufactured by Fujifilm Corporation, thickness 80 μm) was attached to the opposite side to prepare a polarizing plate 1. A polarizer was laminated on the side of the polarizer protective film on which the anti-reflection layer was not laminated to prepare a polarizing plate. The polarizing plate on the viewing side of a SONY BRAVIA KDL-40W920A (a liquid crystal display device having a light source that emits excitation light and a backlight light source containing quantum dots) was replaced with the above polarizing plate 1 so that the polyester film was on the opposite side (distal) to the liquid crystal to prepare a liquid crystal display device. The polarizing plate 1 was replaced so that the direction of the transmission axis was the same as that of the polarizing plate before replacement.

[0112] Example 2 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 2.

[0113] Example 3 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 3.

[0114] Example 4 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 4.

[0115] Example 5 A liquid crystal display device was produced in the same manner as in Example 1, except that the polarizer protective film 4 was used in place of the polarizer protective film 1 and was attached so that its fast axis was parallel to the transmission axis of the polarizer.

[0116] Example 6 A liquid crystal display device was produced in the same manner as in Example 1, except that the polarizer protective film 1 was replaced with the polarizer protective film 7.

[0117] Example 7 A liquid crystal display device was produced in the same manner as in Example 1, except that Polarizer Protective Film 1 was replaced with Polarizer Protective Film 8.

[0118] Example 8 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 9.

[0119] Example 9 A liquid crystal display device was produced in the same manner as in Example 1, except that the polarizer protective film 1 was replaced with the polarizer protective film 12.

[0120] Comparative Example 1 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 5.

[0121] Comparative Example 2 A liquid crystal display device was produced in the same manner as in Example 1, except that the Polarizer Protective Film 1 was replaced with the Polarizer Protective Film 6.

[0122] Comparative Example 3 A liquid crystal display device was produced in the same manner as in Example 1, except that the polarizer protective film 1 was replaced with the polarizer protective film 10.

[0123] Comparative Example 4 A liquid crystal display device was produced in the same manner as in Example 1, except that the polarizer protective film 1 was replaced with the polarizer protective film 11.

[0124] The liquid crystal display devices obtained in the respective Examples were subjected to measurement of rainbow spots, and the results are shown in Table 1 below.

[0125] [Table 1] [Industrial Applicability]

[0126] The liquid crystal display device and polarizing plate of the present invention can ensure good visibility with the occurrence of rainbow-like color spots significantly suppressed at any angle, and thus will make a great contribution to the industrial world.

Claims

1. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, The backlight light source includes a light source that emits excitation light and quantum dots, At least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer, The polyester film has an in-plane retardation of 1500 nm or more and 30000 nm or less, An anti-reflection layer or a low-reflection layer is laminated on at least one surface of the polyester film, a laminate including the polyester film and the antireflection layer, the surface reflectance at a wavelength of 550 nm measured from the surface on the antireflection layer side is 2.0% or less; Or, In a laminate including the polyester film and the low reflection layer, the surface reflectance at a wavelength of 550 nm measured from the surface on the low reflection layer side is less than 5%. LCD display device.

2. A liquid crystal display device having a backlight source, two polarizing plates, and a liquid crystal cell disposed between the two polarizing plates, the backlight light source has an emission spectrum having peak tops in the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 780 nm or less, and a half-value width of each peak is 5 nm or more and 80 nm or less, At least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer, The polyester film has an in-plane retardation of 1500 nm or more and 30000 nm or less, An anti-reflection layer or a low-reflection layer is laminated on at least one surface of the polyester film, a laminate including the polyester film and the antireflection layer, the surface reflectance at a wavelength of 550 nm measured from the surface on the antireflection layer side is 2.0% or less; Or, In a laminate including the polyester film and the low reflection layer, the surface reflectance at a wavelength of 550 nm measured from the surface on the low reflection layer side is less than 5%. LCD display device.

3. 3. The liquid crystal display device according to claim 2, wherein the backlight light source has emission spectrum peak tops in the wavelength regions of 400 nm or more and less than 495 nm, 495 nm or more and less than 600 nm, and 600 nm or more and 750 nm or less, and the half width of each peak is 5 nm or more and 80 nm or less.

4. 4. The liquid crystal display device according to claim 1, wherein at least one of the polarizing plates has a polyester film laminated on at least one surface of a polarizer such that an angle between a transmission axis of the polarizer and a fast axis of the polyester film is −15 degrees to 15 degrees.

5. 5. The liquid crystal display device according to claim 1, wherein the polyester film has a ratio (Re / Rth) of retardation (Re) to retardation in a thickness direction (Rth) of 0.2 or more and 2.0 or less.

6. 6. The liquid crystal display device according to claim 1, further comprising another layer between the antireflection layer and / or the low reflection layer and the polyester film.

7. 6. The liquid crystal display device according to claim 1, further comprising an antiglare layer between the antireflection layer and / or low reflection layer and the polyester film.

Citation Information

Patent Citations

  • Polarizing plate protection film, polarizing plate and liquid crystal display apparatus using same

    JP2009014886A

  • Liquid crystal display device and polarizing plate-protecting film

    JP2013079993A

  • Optical laminate, polarizing plate and image display device

    JP2014026123A

  • Illumination device and display apparatus

    JP2014165116A

  • Liquid crystal display device

    JP2015215577A